Macro-Turbulent Flow and Its Impacts on Sediment Transport Potential of a Subarctic River during Ice-Covered and Open-Channel Conditions - Eliisa Lotsari; Michael Dietze; Maria Kämäri; Petteri Alho; Elina Kasvi (Water, 2020)
Macro-turbulent flows (i.e., coherent flow structures reaching through the whole water column), have not been studied widely in northern seasonally frozen rivers during both open-channel and ice-covered flow conditions. Thus, we aim: (1) to detect and compare the macro-turbulent flow, both at open-channel and ice-covered flow conditions; (2) to explore spatial variation of macro-turbulent flow characteristics within a meander bend; and (3) to detect the effects of near-bed layer velocity fluctuation on bedload transport during differing overall flow conditions. The analyses are based on 5–10 min-long acoustic Doppler current profiler (ADCP) measurements from a subarctic river. The ice-covered low flow, and open-channel higher and lower flow conditions were measured over the period of 2016 to 2020. This study found that macro-turbulent flow existed at all measurement locations under both open-channel and ice-covered flow conditions. Macro-turbulent flow was most consistent and obvious in the streamwise velocity component, and in particular at the inlet and outlet of the investigated meander bend. During all seasons, the near-bed velocities consistently exceeded the sufficient amount for sediment transport. At inlet and outlet areas, the greatest near-bed velocity fluctuation across the critical threshold for sediment transport coincided with the measurement times having frequent macro-turbulent flow.